Particularities of Older Patients with Obstructive Sleep Apnea and Heart Failure with Mid-Range Ejection Fraction - Carmen Loredana Ardelean; Sorin Pescariu; Daniel Florin Lighezan; Roxana Pleava; Sorin Ursoniu; Valentin Nadasan; Stefan Mihaicuta (Medicina, 2019)
Background and objectives: Obstructive sleep apnea syndrome (OSAS) and heart failure (HF) are increasing in prevalence with a greater impact on the health system. The aim of this study was to assess the particularities of patients with OSAS and HF, focusing on the new class of HF with mid-range ejection fraction (HFmrEF, EF = 40%−49%), and comparing it with reduced EF (HFrEF, EF < 40%) and preserved EF (HFpEF, EF ≥ 50%). Materials and Methods: A total of 143 patients with OSAS and HF were evaluated in three sleep labs of “Victor Babes” Hospital and Cardiovascular Institute, Timisoara, Western Romania. We collected socio-demographic data, anthropometric sleep-related measurements, symptoms through sleep questionnaires and comorbidity-related data. We performed blood tests, cardio-respiratory polygraphy and echocardiographic measurements. Patients were divided into three groups depending on ejection fraction. Results: Patients with HFmrEF were older (p = 0.0358), with higher values of the highest systolic blood pressure (mmHg) (p = 0.0016), higher serum creatinine (p = 0.0013), a lower glomerular filtration rate (p = 0.0003), higher glycemic levels (p = 0.008) and a larger left atrial diameter (p = 0.0002). Regarding comorbidities, data were presented as percentage, HFrEF vs. HFmrEF vs. HFpEF. Higher prevalence of diabetes mellitus (52.9 vs. 72.7 vs. 40.2, p = 0.006), chronic kidney disease (17.6 vs. 57.6 vs. 21.5, p < 0.001), tricuspid insufficiency (76.5 vs. 84.8 vs.59.1, p = 0.018) and aortic insufficiency (35.3 vs.42.4 vs. 20.4, p = 0.038) were observed in patients with HFmrEF, whereas chronic obstructive pulmonary disease(COPD) (52.9 vs. 24.2 vs.18.3, p = 0.009), coronary artery disease(CAD) (82.4 vs. 6.7 vs. 49.5, p = 0.026), myocardial infarction (35.3 vs. 24.2 vs. 5.4, p < 0.001) and impaired parietal heart kinetics (70.6 vs. 68.8 vs. 15.2, p < 0.001) were more prevalent in patients with HFrEF. Conclusions: Patients with OSAS and HF with mid-range EF may represent a new group with increased risk of developing life-long chronic kidney disease, diabetes mellitus, tricuspid and aortic insufficiency. COPD, myocardial infarction, impaired parietal kinetics and CAD are most prevalent comorbidities in HFrEF patients but they are closer in prevalence to HFmrEF than HFpEF.